Implementation of Restorative Justice on Traffic Accident Crimes Committed by Children in the Legal Area of the Gorontalo City Police - Podungge, Alamsyah; Darmawati, Darmawati; Nur, Rafika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to determine the Implementation of Restorative Justice in Traffic Accident Crimes Committed by Children in the Gorontalo City Police Department and the Constraining or Inhibiting Factors in the Implementation of Restorative Justice in the Gorontalo City Police Department. This study uses the Juridical Sociological research method, Juridical Sociological is a legal research using secondary data as its initial data, which is then continued with primary data in the field or on the community, examining the effectiveness of a Regulation and research that wants to find a relationship (correlation) between various symptoms or variables, as a data collection tool consisting of document studies or library materials and interviews (questionnaires). The results of the study show; The implementation of restorative justice in resolving traffic accident cases in the Gorontalo City Police Department jurisdiction has been in accordance with the provisions of laws and regulations, especially Perpol Number 8 of 2021, which is carried out after a request for a peaceful settlement of the case and an agreement from the perpetrator and victim signed by all parties involved in the traffic accident which is then followed up by investigators until a Termination of Investigation Order is issued. Obstacles or Constraints that arise in the Implementation of restorative justice, namely; first is the legal factor. Then the second is the factor from the perpetrator's and victim's families who have not reached a peace agreement. And the last is the Facilities and Infrastructure Factor. Law enforcers cannot work well if they are not equipped with adequate facilities and infrastructure.